2015
DOI: 10.1134/s0026261715030200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of organophosphate metabolism in cyanobacteria. A review

Abstract: Cyanobacteria sense the environmental phosphate level and respond accordingly with the help of a two component regulatory system SphS SphR orthologous to PhoR PhoB of E. coli, where SphS act as a sensor kinase and SphR as a response regulator. Under phosphate limiting condition SphS SphR regulates the expression of many genes including genes which do not have the direct role in metabolism and transport of phosphate. Thus there is some crosstalk mechanism which connects this regulatory system to the other metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 64 publications
(92 reference statements)
1
16
0
3
Order By: Relevance
“…When N abundance is low, 2-oxoglutarate (2-OG) may increase, and this could bind to a complex called PII-PipX and breaks this association, allowing the disassociation of PipX, and the formation of PipX-NtcA. PipX is a coactivator of NtcA, and it is suggested that it can stabilize NtcA and would help to recruit RNA polymerase (Tiwari et al, 2015;Kaushik et al, 2016;Giner-Lamia et al, 2017). PO 4 3− is represented as Pi.…”
Section: Differences In Nutrient Kinetics In Diazotrophs At Differentmentioning
confidence: 99%
“…When N abundance is low, 2-oxoglutarate (2-OG) may increase, and this could bind to a complex called PII-PipX and breaks this association, allowing the disassociation of PipX, and the formation of PipX-NtcA. PipX is a coactivator of NtcA, and it is suggested that it can stabilize NtcA and would help to recruit RNA polymerase (Tiwari et al, 2015;Kaushik et al, 2016;Giner-Lamia et al, 2017). PO 4 3− is represented as Pi.…”
Section: Differences In Nutrient Kinetics In Diazotrophs At Differentmentioning
confidence: 99%
“…Species that fix atmospheric nitrogen increase its concentration in the soil. Cyanobacteria possess various environmental adaptations, including the ability to obtain all forms of phosphorus from the environment (Tiwari et al 2015 ; Lipok et al 2007 ). The secretion of enzymes responsible for the assimilation of phosphorus outside the cell is one of the ways to obtain this nutrient (Ravi and Balakumar 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fósforo é o décimo primeiro elemento mais abundante na crosta terrestre, mas devido à sua alta reatividade, permanece indisponível aos microrganismos (TIWARI et al, 2015). Figura 3 -Organização proposta para os 14 polipeptídeos codificados pelo operon phn em E. coli.…”
Section: Regulon Pho: Operon Phnunclassified
“…Estudos posteriores da degradação de fosfonatos biogênicos identificaram quatro enzimas catabólicas principais e suas vias: C-P liase, fosfonoacetaldeído hidrolase (fosfonatase), fosfonoacetato hidrolase e fosfonopiruvato hidrolase, sendo glifosato degradado apenas pela primeira (VILLARREAL-CHIU et al, 2007). C-P liases e fosfonatases são as duas principais vias pelas quais moléculas de fosfonatos são metabolizados, sendo a primeira predominante entre os microrganismos (TIWARI et al, 2015). C-P liases são as únicas enzimas com reconhecida capacidade de quebrar as moléculas de glifosato e AMPA (SVIRIDOV et al, 2012).…”
Section: Vias De Degradação De Glifosatounclassified
See 1 more Smart Citation